The influence of foreign debt, foreign direct investment, exports, and labor on economic growth in ASEAN member countries - Sinaga, Murbanto; Manalu, Angelia Yosefira; Zalukhu, Rika Surianto; Collyn, Daniel; Hutauruk, Rapat Piter Sony (Asian Development Policy Review, 2025)
This study aims to analyze the impact of foreign debt, foreign direct investment (FDI), exports, and labor on economic growth measured by gross domestic product (GDP) in five ASEAN member countries, including Indonesia, Malaysia, Thailand, Vietnam, and the Philippines. This quantitative research uses panel data regression methods, combining time series and cross-sectional data from 2008 to 2018. The data were analyzed using the Common Effect Model (CEM) method. The results show that simultaneously, foreign debt, foreign direct investment, exports, and labor have a significant effect on economic growth. The analysis reveals that foreign debt and FDI have positive and significant impacts, exports have a significantly negative impact, and labor has a statistically insignificant impact on economic growth. The findings suggest that effective management of foreign debt, promotion of FDI, and investment in exports and labor development are key to sustaining economic growth in the ASEAN region. This study provides insights for policymakers to balance foreign debt with productive investments and to attract FDI to sectors that enhance export potential and labor productivity. It further provides references for ASEAN countries in managing debt, attracting investment, optimizing exports, and improving the quality of the workforce to achieve sustainable and inclusive economic growth.